DETERMINANTS OF NON-PERFORMING LOANS (NPL) IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Rani Safitri; Isni Andriana; Sulastri Sulastri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the factors that influence non-performing loans in banking companies listed on the Indonesian stock exchange. The population in this study are banking companies on the Indonesia Stock Exchange for the period 2018 - 2022 with a total of 150 companies with a total sample of 30 companies. The sampling technique was purposive sampling. The data collection technique uses documentation from financial reports published on the IDX's official website, namely.idx.co.id.The analysis used is multiple linear regression analysis with panel data. The results of this study indicate that the loan-to-deposit ratio have a significant positive effect on non-performing loans, and capital adequacy ratio have a significant negative effect on non-performing loans, and inflation have no effect on non-performing loans.